Does resisted sprint training acutely enhance sprint mechanics? - Harrison, A. J.; Whelan, N.; O'Regan, C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Resistance sprint training with sledges and harnesses is often used by athletes to induce an acute enhancement in performance during recovery. Such enhancements are similar to post-activation potentiation (PAP) effects found in complex training. The methods used to detect PAP are variable across studies. The aim of this study was to compare the results of the typical error method of analysis with conventional repeated measures ANOVA on data obtained from a resisted sprint training. The results showed that the ANOVA method found many significant differences between pre-test and post-test means but the typical error method showed relatively few incidences of fatigue-potentiation patterns across any subjects. This suggests that the ANOVA may be an inappropriate analysis technique for examining fatigue potentiation effects.